Nanoscale Distribution of Sulfonic Acid Groups Determines Structure and Binding of Water in Nafion Membranes - Ling, Xiao (Angew Chem Int Ed Engl, 2016)
The connection between the nanoscale structure of two chemically equivalent, yet morphologically distinct Nafion fuel‐cell membranes and their macroscopic chemical properties is demonstrated. Quantification of the chemical interactions between water and Nafion reveals that extruded membranes have smaller water channels with a reduced sulfonic acid head group density compared to dispersion‐cast membranes. As a result, a disproportionally large amount of non‐bulk water molecules exists in extruded membranes, which also exhibit larger proton conductivity and larger water mobility compared to cast membranes. The differences in the physicochemical properties of the membranes, that is, the chemical constitution of the water channels and the local water structure, and the accompanying differences in macroscopic water and proton transport suggest that the chemistry of nanoscale channels is an important, yet largely overlooked parameter that influences the functionality of fuel‐cell membranes.